Prenatal ultrasound diagnosis of cleft palate without cleft lip, the new ultrasound semiology. (17th August 2020) - Faure, Jean Michel; Mousty, Eve; Bigorre, Michèle; Wells, Constance; Boulot, Pierre; Captier, Guillaume; Fuchs, Florent
Abstract: Objectives: The aim of this study was to define the prenatal ultrasound semiology of cleft palate without cleft lip using 3D visualization of the fetal palate. Methods: A prospective longitudinal study was performed in our University Hospital Center from 2011 to 2018. The fetal secondary palate was studied in 3D, starting with 2D axial transverse ultrasound view. We defined a cleft palate as a disruption of the horizontal plate of the palatine bone of the secondary palate. Prenatal findings were correlated to anatomic postnatal examinations performed by a paediatric plastic surgeon. Results: Forty‐three cases of cleft palate without cleft lip were prenatally diagnosed, of whom 34 were associated with malformations. We defined four types of disruptive appearances: isolated nonvisualization of the posterior nasal spine; partial‐disruption or cleft velum; complete disappearance or V‐shaped cleft palate; and complete disappearance or U‐shaped cleft palate. The adjusted kappa coefficient, between prenatal and postnatal evaluation, was 0.88 (95% CI: 0.79‐0.97), corresponding to an excellent agreement. Conclusions: Using a strictly axial transverse ultrasound view, visualization of the secondary fetal palate enables to diagnose a cleft palate without cleft lip. This method offers a prenatal anatomic classification of cleft palate with a high level of concordance to postnatal findings.